Comparison of cytokine production in mice inoculated with messenger RNA vaccines BNT162b2 and mRNA‐1273. (30th December 2022) - Nakayama, Tetsuo; Sawada, Akihito; Ito, Takeshi
Abstract: Two messenger RNA (mRNA) vaccines of BNT162b2 and mRNA‐1273 were licensed. The most common adverse event is regional pain at the injection site in 80%. As systemic reactions, fatigue and headache were noted in 40%–60% and febrile illness in 10%–40% of the recipients. To investigate the mechanism of adverse events, cytokine profiles were investigated in mice. Muscle tissue and serum samples were obtained on days 0, 1, 3, 5, and 7, and at 2 and 4 weeks after the first dose. The second dose was given 4 weeks after the first dose and samples were obtained. After inoculation with 0.1 mL of mRNA‐1273, IFN‐γ and IL‐2 were detected in muscle tissues and serum samples on day 1 of the second doses, and similar profiles were observed for IL‐4, IL‐5, and IL‐12 production. mRNA‐1273 induced higher levels of Th1 and Th2 cytokines. TNF‐α was induced in muscle tissues on day 1 of the first dose and enhanced on day 1 of the second dose after inoculation with BNT162b2 and mRNA‐1273. IL‐6 was also detected in muscle tissue on day 1 of the first dose, but it decreased after day 3, and enhanced production was demonstrated on day 1 of the second dose. Granulocyte colony‐stimulating factor in muscle tissues showed a similar profile. The induction of inflammatory cytokines in the mouse model is related to the cause of adverse events in humans, with a higher incidence of adverse events after the second dose.